• 2022-06-06
    In $G(x)=a_0+a_1 x_ +a_2 x^2+..+a_n x^n+⋯$, generating function is concerned of:
    A: Variable x
    B: Target function G(x)
    C: Coefficient ai
  • C

    举一反三

    内容

    • 0

      下列推导正确的是 。 A: (1) F(x)→G(x) 前提引入 (2)∃xF(x)→G(x) (1)EG B: (1)F(a)→G(x) 前提引入 (2)∃x(F(x)→G(x)) (1)EG C: (1) F(a)→G(x) 前提引入 (2)∃y(F(y)→G(x)) (1)EG D: (1) F(a)→G(x) 前提引入 (2)∃xF(x)→G(x) (1)EG

    • 1

      已知集合M={x|x2<4},N={x|x2-2x-3<0},则集合M∪N 。 A: {x|x<-2} B: {x|x>3} C: {x|-1<x<2} D: {x|2<x<3}

    • 2

      下列各选项中,函数相同的是( )。 A: \(<br/>f(x) = \ln {x^2},g(x) = 2\ln x \) B: \(<br/>f(x) = x,g(x) = \sqrt { { x^2}} \) C: \(<br/>f(x) = \sqrt { { x^2}} ,g(x) = \left| x \right| \) D: \(<br/>f(x) = { { {x^2} - 1} \over {x - 1}},g(x) = x + 1 \)

    • 3

      【单选题】若 f ( x ) = ( x − 1 ) x 2 − 1 2 , g ( x ) = x − 1 x + 1 ,则? A. f ( x ) = g ( x ) "> f ( x ) = g ( x ) B. lim x → 1 f ( x ) = g ( x ) "> lim x → 1 f ( x ) = g ( x ) C. lim x → 1 f ( x ) = lim x → 1 g ( x ) "> lim x → 1 f ( x ) = lim x → 1 g ( x ) D. 以上等式均不成立

    • 4

      设$f(x),g(x),h(x)$是三个实系数多项式,且$$f^{2}(x)=xg^{2}(x)+xh^{2}(x)$$则$f(x),g(x),h(x)$满足条件()。 A: $f(x)=g(x),f(x)\not=h(x)$; B: $f(x)=g(x)=h(x)=0$; C: $f(x)\not=g(x),g(x)\not=h(x)$; D: $f(x)\not=g(x),g(x)=h(x)$.